3-2(4-x)=5(x+1)+2

Simple and best practice solution for 3-2(4-x)=5(x+1)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-2(4-x)=5(x+1)+2 equation:


Simplifying
3 + -2(4 + -1x) = 5(x + 1) + 2
3 + (4 * -2 + -1x * -2) = 5(x + 1) + 2
3 + (-8 + 2x) = 5(x + 1) + 2

Combine like terms: 3 + -8 = -5
-5 + 2x = 5(x + 1) + 2

Reorder the terms:
-5 + 2x = 5(1 + x) + 2
-5 + 2x = (1 * 5 + x * 5) + 2
-5 + 2x = (5 + 5x) + 2

Reorder the terms:
-5 + 2x = 5 + 2 + 5x

Combine like terms: 5 + 2 = 7
-5 + 2x = 7 + 5x

Solving
-5 + 2x = 7 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-5 + 2x + -5x = 7 + 5x + -5x

Combine like terms: 2x + -5x = -3x
-5 + -3x = 7 + 5x + -5x

Combine like terms: 5x + -5x = 0
-5 + -3x = 7 + 0
-5 + -3x = 7

Add '5' to each side of the equation.
-5 + 5 + -3x = 7 + 5

Combine like terms: -5 + 5 = 0
0 + -3x = 7 + 5
-3x = 7 + 5

Combine like terms: 7 + 5 = 12
-3x = 12

Divide each side by '-3'.
x = -4

Simplifying
x = -4

See similar equations:

| 4mn-6m+5n-3m+4n-5mn= | | =x^2+19x+2 | | 2(x-3)-(x-2)=2x+3 | | 1-7y=-1 | | x-8.7=6.8 | | -9.3x=55.8 | | m+33=13 | | 24(2x-1)=6(x+3)+3 | | 2r=-8 | | =2-3x+2x^2-x^3 | | (4x-1)(x+2)=x(2x-3)-10 | | -8(2b+4)+(17b-6)=0 | | 2.5q-4.8-4.1q=-2.6q-4.7 | | 4-(2-3x)=6x-(4x+3) | | 0=-8+3z | | 2.5q-4.8q-4.1q=-2.6q-4.7 | | =2x^7+4x^6-6x^5+4x^4 | | 4(0)+y=-14 | | 4(-2)+y=-14 | | 4(-6)+y=-14 | | (y+3)(y+1)=2y(y+3) | | x^3-6*x^2+9*x-4=0 | | x^2-7x+264=0 | | x^2+8-7x+256=0 | | 36z^2-4=0 | | 1+8x=46-64x | | -0.2(x+3)=0.3(x+11) | | 9x(x)+47x+44=0 | | 2x(x)+x-2x-1=3x+6+9x | | 5x^2-60x+15=0 | | 3x^2+9x-36=0 | | a^2b-25b= |

Equations solver categories